CONSUMER BEHAVIOUR: READY-TO-EAT FOOD IN PENINSULAR MALAYSIA BASED ON FOOD-RELATED LIFESTYLE - Ana Batrisyia Azman; NorSyakirah Mazlan; Fatimah Abd Ghani; Noorazlin Ramli; Norhayati Mat Yusoff (Journal of Islamic, Social, Economics and Development, 2023)
Demand for ready-to-eat (RTE) food is on the rise in Malaysian cities as a result of shifting lifestyles. The purpose of this research is to determine what motivates Peninsular Malaysians to buy and consume RTE foods, as well as what factors have the greatest influence on these consumers. A quantitative methodology was used, and a descriptive research design informed data collection and analysis. Because of this, the study's goals could be met. Data from 385 Peninsular Malaysian clients was gathered through the use of convenience sampling and online distributed, closed-ended structured questionnaires. This research focuses on the Federal Territory of Kuala Lumpur and the five other states of Selangor, Malacca, Perak, Johor, and Penang, which represent the six most economically developed states in Malaysia. Significant changes to urban lifestyle have occurred in these areas as urbanisation has progressed. The impact of ready-to-eat food on customers' eating habits was investigated by looking at four factors: health, flavour, convenience, and tradition. This research found that among the six states of Peninsular Malaysia under consideration, the convenience of ready-to-eat (RTE) foods was the primary factor influencing consumer behaviour. Hence, the researcher believes that knowing how customers feel about RTE food and the results reported in this paper can aid RTE food makers in formulating effective marketing strategies.